Réponses

2012-09-12T20:24:04+02:00
2012-09-12T20:27:14+02:00

la multiplication est prioritaire 

donc tu calcule d'abord (x-2)(x+4)=  x*x+x*4-2*x-2*4

                                                 = x²+4x-2x-8

en suite (x-2)(x+8) = x*x+x*8-2*x-2*8

                             =x²+8x-2x-16

en suite tu fais la somme de tout donc

 ( x²+4x-2x-8)+(x²+8x-2x-16)=(x²+2x-8)+(x²+6x-8)

                                           =x²+2x-8+x²+6x-8

                                           =2x²+8x-16